Local Commitment and Global Reach: Advancing Sustainable Capacity Building in Higher Education - Sabine O’Hara; Sigamoney Naicker (World, 2022)
Universities play a crucial role in building the economic development capacity for their communities and regions. Their capacity building role is typically defined by contributions to the economic bottom line of the community and region where a university is located. This kind of capacity building may find itself in conflict with the long-term sustainable development needs of the region and with the responsibility of the university itself. Sustainable capacity building may require strategies that focus on the specific social, cultural, environmental, and physical context of a university’s location beyond purely economic capacity goals. To achieve sustainable development outcomes, universities must advance an understanding of the context conditions within which they are located. At least three context systems are relevant to this view of development: the economy, society and culture, and the environment with its physical, biological, and ecological context conditions. Each of these context systems is characterized by distinct time frames, spatial configurations, rules, and success measures. A focus on economic development outcomes reflects only one subsystem’s rules, behaviors, and success measures. By analyzing two case study examples from the United States and South Africa, we offer a framework for universities to advance sustainability objectives that correspond to their broader responsibilities. We argue that in order to meet these broader responsibilities, universities must first commit to giving expression to their own local context through the voices and lived realities of students and residents. Since universities build the brain trust of communities and regions around the world, they play an essential role in strengthening global sustainability goals by building the local capacity of their communities and regions.